The SEM-PLS Model of Post-FMD Farmer Welfare in Indonesia: Integration of Social, Economic, and Psychological Factors - Kusuma, Ananta Winendra Surya Kusuma; Putritamara, Jaisy Aghniarahim; Annisa’, Rofiatin (Journal of Agriprecision & Social Impact, 2026)
The Foot-and-Mouth Disease (FMD) outbreak has inflicted severe multidimensional disruptions on dairy farming communities, yet limited research has systematically examined how social, economic, and psychological impacts collectively shape farmer welfare in post-outbreak contexts, particularly in developing countries. This study aims to investigate the simultaneous effects of social, economic, and psychological impacts on the welfare of dairy farmers following the FMD outbreak in Indonesia, and to extend theoretical frameworks of welfare and resilience to the context of livestock disease crises. A quantitative survey was conducted with 150 dairy farmers in Pujon District, Malang Regency—one of the areas most severely affected by the 2022 FMD outbreak. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement model results was assessed for reliability and validity, while the structural model tested the hypothesized relationships. All three impact dimensions demonstrated significant positive effects on farmer welfare: social impact (β = 0.640, t = 4.431, p < 0.001), economic impact (β = 0.635, t = 4.487, p < 0.001), and psychological impact (β = 0.647, t = 4.143, p < 0.001). The model explained 95.5% of the variance in farmer welfare (R² adjusted = 0.955), indicating exceptional explanatory power. Factor loadings revealed that mutual assistance (0.990), loss of assets (0.986), and business insecurity (0.981) were the strongest indicators of social, economic, and psychological impacts, respectively. Farmer welfare in post-FMD contexts emerges from the synergistic interplay of social solidarity, economic pragmatism, and psychological resilience. The findings extend welfare utility and post-traumatic growth theories to livestock disease settings and provide evidence-based foundations for integrated post-disaster interventions targeting smallholder farmers in developing countries.